Ilmu Mauhibah sebagai Syarat Penafsir Al-Quran - Ruslan (Interdisciplinary Explorations in Research Journal, 2024)
He scholars differ in determining the conditions for interpreting the Koran. One of the 15 conditions put forward by al-Suyuthi in his book al-Itqan fi Ulum al-Qur'an is the Knowledge of Mauhibah. Al-Suyuthi said that Mauhibah knowledge is knowledge that is given directly by Allah to anyone who practices his knowledge. Later generations of scholars often quote and refer to al-Suyuthi, including Ahmad al-Syirbashi, Basyuni Faudah, Muhammad Husain al-Dzahabi. Meanwhile, mutaqaddimin scholars such as al-Ghazali, al-Maturidi, etc. expressed various opinions. Al-Maturidi (born around 238 H/852 M- d.333H/944 M) equated the science of mauhibah with the science of laduni with the same definition. Al-Ghazali put forward three views, including that knowledge is obtained because of luck from Allah. If we follow the opinion of al-Ghazali (d. 505 H/1111 AD) and al-Maturidi, the science of mauhibah is the science of laduni; There are similarities with the science of kasbiyah, it is not merely an abundance from God but there is effort from humans. Scholars differ in their opinions about how to obtain mauhibah knowledge. There are those who get it directly from Allah and there are also those who think indirectly, namely using the riyadhah and muraqabah methods Para ulama berbeda dalam menetapkan Syarat-syarat bagi penafsir Alquran. Satu dari 15 syarat yang dikemukakan oleh al-Suyuthi dalam kitabnya al-Itqan fi Ulum al-Qur’an adalah Ilmu Mauhibah. Al-Suyuthi mengatakan ilmu Mauhibah tersebut adalah ilmu yang dianugerahkan langsung oleh Allah kepada siapa saja yang mengamalkan ilmunya. Ulama generasi belakangan banyak mengutip dan merujuk kepada al-Suyuthi diantaranya Ahmad al-Syirbashi, Basyuni Faudah, Muhammad Husain al-Dzahabi. Sedangkan ulama mutaqaddimin semisal al-Ghazali, al-Maturidi, dll mengemukakan pendapat yang beragam. Al-Maturidi (lahir sekitar 238 H/852M) menyamakan ilmu mauhibah dengan ilmu laduni dengan definisi yang sama. Al-Ghazali mengemukakan tiga pandangan di antaranya ilmu diperoleh karena mendapat keberuntungan dari Allah. Bila mengikuti pendapat al-Ghazali (w. 505 H/1111 M) dan al-Maturidi (w.333H/944 M) ilmu mauhibah adalah ilmu laduni; ada kemiripan dengan ilmu kasbiyah tidak semata-mata limpahan dari Tuhan tapi ada usaha dari manusia. Ulama berbeda pendapat tentang cara memperoleh ilmu mauhibah. Ada yang memperolehnya langsung dari Allah dan ada juga yang berpendapat tidak langsung, yakni memakai metode riyadhah dan muraqabah.